Analisis Apresiasi Berbentuk Bintang Metode Pembelajaran Kelas 1 di SDN 137 Pekanbaru - Dita Darma Aulia; Anggik Anggraini; Elsi Olivia; Laura Meisy Tania; Dea Mustika (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the application of star-shaped appreciation as a learning method in grade I elementary school students. Star-shaped appreciation is used as a form of positive reinforcement to increase students' motivation, participation, and learning attitudes during the learning process. The research method used is descriptive qualitative research with the research subjects of grade I students and classroom teachers. Data collection techniques include observation, interviews, and documentation. The results of the study show that giving star-shaped appreciation is able to increase students' enthusiasm for learning, encourage students' courage to actively participate, and create a more fun and conducive learning atmosphere. In addition, this method also helps teachers in managing the classroom and instilling discipline and responsibility values in students. However, the application of star-shaped appreciation needs to be done fairly and consistently so as not to cause jealousy among students. Based on the results of the study, it can be concluded that star-shaped appreciation is an effective learning method and is suitable for students in grade I of elementary school.